2006
DOI: 10.2174/156802606777323647
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationships of KATP Channel Openers

Abstract: Given their many physiological functions, K(ATP) channels represent promising drug targets. Sulfonylureas like glibenclamide block K(ATP) channels; they are used in the therapy of type 2 diabetes. Openers of K(ATP) channels (KCOs) e.g. relax smooth muscle and induce hypotension. KCOs are chemically heterogeneous and include as different classes as the benzopyrans, cyanoguanidines, thioformamides, thiadiazines and pyridyl nitrates. Examples for new chemical entities more recently developed as KCOs include cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 77 publications
1
15
0
Order By: Relevance
“…Interestingly, a clinical trial for T2D with the IL-1R antagonist anakinra has shown some promise, as anakinra improved glycemia and beta-cell secretory function, and reduced markers of systemic inflammation. 81 Furthermore, the common anti-diabetic drug, glibenclamide (also known as glyburide), which operates by inhibiting ATP-sensitive potassium channels, 82 was shown to inhibit NLRP3 inflammasome assembly and caspase-1 activation, suggesting that pharmacological modulation of the inflammasome-IL-1b axis might be a viable approach for the treatment of T2D. 83 A second drug most commonly used for the treatment of T2D is metformin, which acts by activating AMPK and the upstream kinase LKB1 (reviewed in Hardie 84 ), arguing that its efficacy might be partially mediated by modulating inflammasome activity.…”
Section: The Inflammasome and The Metabolic Syndromementioning
confidence: 99%
“…Interestingly, a clinical trial for T2D with the IL-1R antagonist anakinra has shown some promise, as anakinra improved glycemia and beta-cell secretory function, and reduced markers of systemic inflammation. 81 Furthermore, the common anti-diabetic drug, glibenclamide (also known as glyburide), which operates by inhibiting ATP-sensitive potassium channels, 82 was shown to inhibit NLRP3 inflammasome assembly and caspase-1 activation, suggesting that pharmacological modulation of the inflammasome-IL-1b axis might be a viable approach for the treatment of T2D. 83 A second drug most commonly used for the treatment of T2D is metformin, which acts by activating AMPK and the upstream kinase LKB1 (reviewed in Hardie 84 ), arguing that its efficacy might be partially mediated by modulating inflammasome activity.…”
Section: The Inflammasome and The Metabolic Syndromementioning
confidence: 99%
“…There are also agents that are able to open K ATP channels [K ATP channel opening drugs (K CO s)]. Intriguingly, not only are some of these agents selective for K ATP but they also exhibit a very broad range of chemical structures: for example, diazoxide is a benzothiadiazine, pinacidil a cyanoguanidine and nicorandil a pyridyl nitrate (Mannhold, ). Agents known to block other K + channels, for example, Ba 2+ and 4‐aminopyridine, are also active on K ATP channels.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years many structural changes have been made, mainly on the nucleus of benzopyran KCOs, in order to find new compounds with a higher selectivity toward specific targets, such as the K ATP channel of pancreatic β-cells or the cardiac mitochondrial K ATP channel, such as the benzopyranylcyanoguanidine derivatives BMS-180448 and BMS-191095. , Until now, most chemical modifications on benzopyran KCOs have been studied at the C4 position (Figure ), but a few cases have regarded the restriction of the conformation of this substituent through its insertion into a spiro-like structure.
1 Left: graphical representation of SAR data for anti-ischemic properties of benzopyran derivatives, adapted with some modifications from Mannhold . Right: general structure of the synthesized spiromorpholone- ( 1a , b and 2b) and spiromorpholine KCOs ( 3a , b and 4b ).
…”
mentioning
confidence: 99%